Search 75,402 tutors
FIND TUTORS
Ask a question
0 0

Evaluate and simplify the following function:

Tutors, please sign in to answer this question.

1 Answer

Dear Katelyn,
 
I'm not sure I understand this perfectly, but I think what you want is
 
f(x-1) = 3*(x - 1)2 - 2*(x - 1) - 3 = 3(x2 -2x + 1) - 2x + 2
 
f(x-1) = 3x2 -6x +3 -2x + 2 = 3x2 - 8x + 5
 
 

Comments

Thank you, William! Only thing missing was the -3 at the end, so I found the answer to actually be 3x2-8x+2. But I now I understand how to find the solution, so thank you for that!

Comment